2017
DOI: 10.1002/2017gl073449
|View full text |Cite
|
Sign up to set email alerts
|

Antenna structures and cloud‐to‐ground lightning location: 1995–2015

Abstract: Spatial analyses of cloud‐to‐ground (CG) lightning occurrence due to a rapid expansion in the number of antenna towers across the United States are explored by gridding 20 years of National Lightning Detection Network data at 500 m spatial resolution. The 99.8% of grid cells with ≥100 CGs were within 1 km of an antenna tower registered with the Federal Communications Commission. Tower height is positively correlated with CG occurrence; towers taller than 400 m above ground level experience a median increase of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
19
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(25 citation statements)
references
References 33 publications
5
19
0
1
Order By: Relevance
“…Especially for shallow lake-effect thundersnow events, the electric field breakdown can happen due to large and tall anthropogenic structures (e.g., wind turbines and television towers) and lightning can occur in a stratiform region, that is, away from the core of convection (Schultz et al, 2018;Steiger et al, 2018). Kingfield et al (2017) showed a positive correlation between tall structures and CG occurrences, where the locations near to taller tower (> 400 m) experienced a median increase of 150% CG lightning density compared to the farther locations. Other past studies also have suggested that the presence of large ice particles (>30 dBZ) or graupel in the mixed-phase region is a good source of lightning electrification (Buechler & Goodman, 1990;Petersen et al, 1996;Williams et al, 1991 etc.).…”
Section: Discussionmentioning
confidence: 99%
“…Especially for shallow lake-effect thundersnow events, the electric field breakdown can happen due to large and tall anthropogenic structures (e.g., wind turbines and television towers) and lightning can occur in a stratiform region, that is, away from the core of convection (Schultz et al, 2018;Steiger et al, 2018). Kingfield et al (2017) showed a positive correlation between tall structures and CG occurrences, where the locations near to taller tower (> 400 m) experienced a median increase of 150% CG lightning density compared to the farther locations. Other past studies also have suggested that the presence of large ice particles (>30 dBZ) or graupel in the mixed-phase region is a good source of lightning electrification (Buechler & Goodman, 1990;Petersen et al, 1996;Williams et al, 1991 etc.).…”
Section: Discussionmentioning
confidence: 99%
“…Lightning at the location of tall man‐made objects has been documented by several investigators in the last few years (e.g., Kingfield et al, ; Schultz et al, ; Warner et al, ). Previous work by Warner et al () showed that the NLDN detected a flash within 50 km and 500 ms prior to upward lightning from a tall object.…”
Section: Discussionmentioning
confidence: 99%
“…A new observational study (Kar and Liou, 2019) indicated that both the land and aerosol effects should be considered to explain the cloud-to-ground lightning enhancements over the urban areas. Kingfield et al (2017) also found that cloud-to-ground lightning enhancements can also be caused by the presence of tall towers. A modeling study showed urban land cover changes increased precipitation over the upstream region but decreased precipitation over the downstream region, while aerosols had the opposite effect by serving as cloud condensation nuclei (Zhong et al, 2015).…”
Section: Introductionmentioning
confidence: 88%